La instrumentalización de la política pública sobre refugio: Procedimiento para determinar la condición de refugiado a través de la visa 12 - IV. (2007 – 2015) - Noroña Martínez, Myrian Elizabeth (2016)
This research will study the instrumentation of refuge as a public policy: the procedure to establish the refugee status through the 12 - IV visa, considering that the refugee status was born in the 1940s (Post - WWII), as a consequence of the war and with the sole purpose to protect the population in a refugee situation, the Geneva Convention was created in 1951 and its Protocol was made in 1967. A refugee obtaining temporary protection in countries close to their own was the result of this process; and Ecuador during the last decades has received 233,049 refugee applications, of which 60,253 were recognized as refugees. Therefore, Ecuador faces a great challenge, based mainly on the necessity to generate public policies, which are focused on to the population that requires international protection.